Validation of the Arabic version of the breastfeeding behavior questionnaire among Lebanese women - Lama Charafeddine; Saadieh Masri; Lama Shamsedine; Lilian Ghandour; Hani Tamim; Nathalie El Khoury; Zahraa Hachem; Mona Nabulsi (BMC, 2020)
Abstract Background The Breastfeeding Behavior Questionnaire (BBQ) assesses women's perceptions of their breastfeeding behavior. It was adapted to several languages and used in different settings, but has not been validated in Arabic-speaking populations. None of the previous studies that used the BBQ in other cultures examined its ability to predict the actual breastfeeding behaviors of mothers postpartum. This study validated the BBQ in a cohort of Lebanese pregnant women between December 2013 and January 2016, and examined whether it can predict exclusive breastfeeding at one, three and six months. Methods The internal consistency reliability and construct validity of the Arabic BBQ (BBQ-A) were tested on 354 pregnant women. Its predictive ability was assessed by correlating the women's BBQ-A scores with their breastfeeding outcomes at one, three and six months post-delivery. Results The BBQ-A had a good internal consistency reliability (Cronbach's alpha = 0.78). Exploratory factor analysis revealed that it is unidimensional. Inter-item correlations ranged between − 0.016 and 0.934, with corrected-item total correlations ranging from 0.273 to 0.678. Perceived positive breastfeeding behavior correlated with positive breastfeeding attitudes, good breastfeeding knowledge and stronger breastfeeding intention supporting its external validity. However, in binomial multivariate logistic regression analysis, the BBQ-A did not predict exclusive breastfeeding at one, three or six months. Conclusions The BBQ-A is a reliable and valid instrument to assess women's perceptions of their breastfeeding behavior in an Arab context. Availability of this instrument is important for investigators conducting breastfeeding research in the Arab world. However, the BBQ-A does not predict exclusive breastfeeding at one, three or six months. Further research on the Breastfeeding Behavior Questionnaire is needed to examine its predictive validity in other cultures.